Application of the Technology Acceptance Model in Information Systems at the Public Administration of Peru - Reyes, Marlene (2020)
Technology Acceptance Model (TAM) is one model that is used by many researchers in order to analyze the technological acceptance that guarantees the success of its implementation. The TAM model has managed to position itself as one of the most used models, to test and validate among existing models for technological acceptance. The main objective of this research is to analyze the adoption of the Document Management System (SGD) that uses Digital Signature technology in Peruvian public entities, incorporating two important constructs into the TAM model: trust and perceived risk. The various studies show that the predictive capacity of these psychological constructs influences in a positive way in agreement with the constructs of the TAM model. The conclusions of the present investigation can improve the service to citizens, which will contribute positively to the decisions of public administration managers, academics, teachers and researchers in this environment.